Effect of forest density on richness and diversity of spring oak gallwasps (sexual generation) at oak forests in West Azarbaijan - Z Bagheri; Javad Eshaghi Rad; M. R Zargaran (مجله جنگل ایران, 2019)
This research was carried out for investigating the effect of stand density on the richness and diversity of spring gallwasps species in Quercus branti stands in Sardasht forest (West Azarbaijan province). The effect of density on the diversity and richness of gallwasps was investigated in three populations with completely sparse, sparse, and relatively dense stands. A total of 30 samples with an area of 400 m2 were arranged to record the quantities of woody species and the type and frequency of gallwasps species. In each sample, the frequency and types of herbaceous species were recorded in 5 subsample (1.5×1.5 m). The results showed that there were eight gallwasps from the Cynipidae family in Sardasht forest. The Shannon evenness index of gallwasps was significantly correlated with the number of coppice, the mean diameter and the mean basal area. The Simpson species index of gallwasps was in correlation with the mean basal area. Furthermore, we found a significant correlation between Shannon species diversity, Shannon evenness, and Simpson species diversity of the herbaceous species and Shannon species diversity, Shannon evenness, Simpson species diversity and Margalef species richness of gallwasps.